Cavity Formation is a Prognostic Indicator for Pathologic Stage I Invasive Lung Adenocarcinoma of ≥3 cm in Size - Chen, Chunji (Med Sci Monit, 2019)
BACKGROUND: We investigated the correlation between cavity formation, prognosis, and tumor stage for pathologic stage I invasive lung adenocarcinomas (IADCs) ≤3 cm in size. MATERIAL/METHODS: 2106 candidates with pathologic stage I IADC were identified from Shanghai Chest Hospital between 2009 and 2014. There were 227 patients who were diagnosed as having cavity formation and another 1879 patients who were not (the non-cavitary lung cancer group). Kaplan-Meier analysis curves were conducted to compare the overall survival (OS) and relapse-free survival (RFS) between these 2 groups. Cox proportional hazards regression was performed to discover the independent risk factors of OS and RFS. Receiver operating characteristic (ROC) curve was done to determine the cutoff value of cavity size for predicting prognosis. Furthermore, subgroup analysis was stratified by the size of tumor and the 8(th) classification of T category. RESULTS: Compared with non-cavitary lung cancer group, patients with cavity formation were found to have a higher prevalence of male patients (P=0.015), older age patients (P=0.039), larger size tumors (P=0.004), and worse cancer relapse (P<0.001). Survival analysis found that patients with cavitary IADC had significantly shorter RFS than those with non-cavitary IADC (P=0.001). Further, subgroup analysis confirmed a significantly worse RFS in cavitary IADC group both in stage T1a (P=0.002) and T1b (P<0.001), but not for stage T1c (P=0.962) and T2a (P=0.364). Moreover, cavity formation was still less of a significant predictor of RFS in multivariable analysis (hazard ratio [HR] 1.810, 95% confidence level [CI] 1.229–2.665, P=0.003). The ROC curve showed that the best cutoff value of maximum diameter of the cavity for judging RFS was 5 mm (sensitivity: 0.500; specificity: 0.783). At the same time, multiple cavities were more likely to lead to recurrence (sensitivity: 0.605; specificity: 0.439). CONCLUSIONS: Cavitary adenocarcinoma was a worse prognostic indicator compared with non-cavitary adenocarcinoma, especially for cavity >5 mm and multiple cavities. Thus, for stage T1a and T1b, cavitary and non-cavitary IADC should be considered separately.